The application of enzymatic fermented soybean effectively regulates associated microbial communities in tea soil and positively affects lipid metabolites in tea new shoots - Zhang, Shuning; Sun, Litao; Shi, Yujie; Song, Yujie; Wang, Yu; Fan, Kai; Zong, Rui; Li, Yusheng; Wang, Linjun; Bi, Caihong; Ding, Zhaotang (Frontiers in Microbiology, 2022)
Compared with traditional organic fertilizer, fermented soybean is a better fertilizer resource in tea plantations. The application of organic fertilizer is a feasible practice to mitigate the soil degradation caused by the overuse of chemical fertilizers, which can effectively regulate soil microbial communities in tea plantations. However, the effects of fermented soybean on soil microbial communities, soil metabolites and metabolites in tea new shoots have not been systematically demonstrated, and their interactions have never been studied. Here, we investigated the responses of the soil microbial community, soil metabolites and metabolites of tea new shoots to urea fertilization (UF), naturally fermented soybean fertilization (NFS) and enzymatic fermented soybean fertilization (EFS), and analyzed the relationships between soil microbes, soil metabolites and metabolites in tea new shoots. The results showed that soil bacterial communities were dominated by Pseudomonas, Romboutsia, Candidatus_Nitrosotalea and Helicobacter, and soil fungal communities were dominated by Peziza, Fusarium, Candida and Cheilymenia at the genus level. In EFS, bacterial genera (Glutamicibacter and Streptomyces) and fungal genera (Candida and Actinomucor) presented high abundances, which were correlated with soil carbohydrate and lipid including D-Mannitol, D-Sorbitol, 9,12-Octadecadienoic acid and (Z)-13-Docosenoic acid. Enzymatic fermented soybean fertilization also affected the lipid metabolites in tea new shoots. Glycerolipids and glycerophospholipids significantly increased in EFS, which positively correlated with some soil microbial communities. Besides, the application of fermented soybean fertilizer could increase the contents of TP, AP and AK, which were also important environmental factors affecting the structure of soil microbial community in tea plantation. It was concluded that fermented soybean fertilization could improve soil nutrition, regulate associated microbial communities, and positively affect lipid metabolites in tea new shoots. This study not only explores the relationships between soil microbes and metabolites in tea plants, but also provides feasible technical guidance to cultivate high-quality tea using soybean as high-grade fertilizer.